2013
DOI: 10.1111/1471-0528.12274
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for obstetric anal sphincter injury after a successful multicentre interventional programme

Abstract: Objective To evaluate and compare the risk profile of sustaining obstetric anal sphincter injuries (OASIS) and associated risks in five risk groups (low to high), after the OASIS rate was reduced from 4.6% to 2.0% following an interventional programme. The main focus of the intervention was on manual assistance during the final part of second stage of labour.Design A multicentre interventional cohort study with before and after comparison.Setting Four Norwegian obstetric departments. after the intervention. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
70
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 38 publications
5
70
1
Order By: Relevance
“…More free text comments were made about ‘chinning’ than any other technique; mostly around unfamiliarity with this method. The introduction of a combination of strategies, including ‘chinning’ to routine care at birth was associated with a significant drop in the OASI rate in Norway 16, 17, 18, 19. It is unclear whether ‘chinning’ by itself had any effect, or whether the decrease was driven by the other ‘hands on’ techniques, and/or by other strategies individually or in combination with each other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More free text comments were made about ‘chinning’ than any other technique; mostly around unfamiliarity with this method. The introduction of a combination of strategies, including ‘chinning’ to routine care at birth was associated with a significant drop in the OASI rate in Norway 16, 17, 18, 19. It is unclear whether ‘chinning’ by itself had any effect, or whether the decrease was driven by the other ‘hands on’ techniques, and/or by other strategies individually or in combination with each other.…”
Section: Discussionmentioning
confidence: 99%
“…Other strategies, including emphasis on selective mediolateral (as opposed to midline) episiotomy, good visualisation of the perineum at birth and communication with the mother regarding slow pushing, were also implemented. With OASI rates decreasing from 4–5 to 1–2%,16, 17, 18, 19 questions about the appropriateness of abandoning traditional perineal support practices have been raised.…”
Section: Introductionmentioning
confidence: 99%
“…& Authors' reply Sir, We acknowledge Mrs Plumb for her interest in our recently published BJOG article. 1 Our study demonstrated the ability of a rapid molecular test to detect Streptococcus agalactiae (GBS) in the vagina of women at delivery, so as to reduce the prescription of useless antimicrobial drugs, in comparison with the current strategy founded on the detection of GBS in the maternal vagina at 35-37 weeks of gestation. In a few cases (three from a total of 225 women), however, the new strategy was impaired by the time needed to perform the test because of the short time between admission and delivery, which resulted in an insufficient dose of amoxicillin (2 grams instead of 3 grams) being administered during labour.…”
mentioning
confidence: 92%
“…In a few cases (three from a total of 225 women), however, the new strategy was impaired by the time needed to perform the test because of the short time between admission and delivery, which resulted in an insufficient dose of amoxicillin (2 grams instead of 3 grams) being administered during labour. 1 Concerning the additional data required by Mrs Plumb, the mean length of time between the admission of pregnant woman and delivery was 9 hours 30 minutes AE 9 hours 38 minutes. In 20 cases from 225 (0.09%), the result of the molecular test was available only after delivery (see figure 2 in the original article).…”
mentioning
confidence: 99%
See 1 more Smart Citation